Inducible Models of Bone Loss. Issue 4 (11th December 2014) - Doucette, Casey R.; Rosen, Clifford J.
Abstract : Bone is an essential organ that not only confers structural stability to the organism, but also serves as a reservoir for hematopoietic elements and is thought to affect systemic homeostasis through the release of endocrine factors as well as calcium. The loss of bone mass due to an uncoupling of bone formation and bone resorption leads to increased fragility that can result in devastating fractures. Further understanding of the effects of environmental stimuli on the development of bone disease in humans is needed, and they can be studied using animal models. Here, we present established and novel methods for the induction of bone loss in mice, including manipulation of diet and environment, administration of drugs, irradiation, and surgically induced hormone deficiency. All of these models are directly related to human cases, and thus, can be used to investigate the causes of bone loss resulting from these interventions. © 2014 by John Wiley & Sons, Inc.